Histopathology An Update - Srivastava, Supriya (IntechOpen, 2018)
This book, "Histopathology-An Update" is a comprehensive book that deals with the latest advances in the field of histopathology. This book will be of help to pathologists, clinicians and researchers in the latest update in histopathology of various organs.